PTH-076 Switching from originator infliximab to CT-P13: a UK single centre experience. (June 2019) - Bhandare, Anirudh Pramod; Crooks, Benjamin; Nigam, Gaurav Bhaskar; Limdi, Jimmy K
Abstract : Introduction and Aims: The infliximab biosimilar (CT-P13) received market authorization for inflammatory bowel disease in late 2016 with the aim of reducing cost and increasing access to therapy. The prospect of 'switching' patients from originator to CT-P13 has concerned clinicians.We present an experience of 'switching' from originator infliximab (IFX-O) to CT-P13 and present efficacy, safety and immunogenicity data from our cohort. Methods: We performed a retrospective review of patients switched from IFX-O to CT-P13 at our center. Disease demographics, clinical course and outcomes were analysed from electronic case records at 8 months and at last follow-up at 13 months. Results: Ninety-six patients (35 female) were 'switched' from IFX-O to CT-P13. Of these 44 had Ulcerative colitis (UC) and 52 had Crohn's disease (CD) with a mean age at diagnosis of 34.7 years (median= 33, IQR = 24.5). Montreal phenotype for UC was Proctitis( E1) = 1, Left sided(E2) = 16, Pancolitis ( E3) = 27 and for CD (L1 = 10, L2 = 12, L3 = 29, L4 = 1) and ( B1 = 27, B2 = 14, B3 = 11), 9 patients had perianal disease. Mean duration of IFX-O treatment before switching was 49.8 months (median = 44, IQR = 52) and on CT-P13 11.5 months (median 13). At switch, 76 patients had a normal CRP (UC = 33, CD = 43), and in 15 patients it was elevated (UC= 10, CD= 5). At 8 months, 72 patients (UC = 34, CD = 38) were in clinical remission (pMayo < 2 and HBI < 5) and 80 patients remained in biochemical remission (UC= 35, CD= 45). In 14 patients (UC= 8, CD= 6 ) CRP increased. Of 51 patients (UC= 21, CD= 30) undergoing endoscopic assessment, 31 achieved mucosal healing (UC =13, CD= 18). At 13 months 69 patients remained on CT-P13. 28% discontinued the drug due to immunogenicity(n=10), loss of response(n=5), surgery(n=5), remission (n=5), side effects (n=2) and 1 patient died of hospital acquired pneumonia. 39 out of 96 patients had therapeutic drug levels checked within a median of 13 months from switch. 27 had sub-therapeutic levels (below 4ug/ml ), 11 of which were switched to another biologic, 5 referred for surgery, 4 had dose escalated to 10 mg/kg, 5 continued CT-P13( 4 with no antibodies seen and 1 with antibodies of 127), one had immunomodulator added and another stopped CT-P13 being in remission. Antibodies to Infliximab were seen in 15 of 39 patients (38.5%), of whom 8 were switched to an alternative biologic, 2 had dose escalation (10 mg/kg IFX), 4 patients stopped IFX with no other intervention and 1 person continued treatment with low antibody titre of 6. Discussion: Biosimilar IFX (CT-P13) was well tolerated. Clinical efficacy and loss of response rates with CT-P13 appears to be similar to IFX-O. This holds promise for a wider adoption of 'switching' to fulfil the purported aims of wider access to treatment at a lower cost.